2015
DOI: 10.2105/ajph.2014.302546
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Liver Disease Mortality With HIV and Overdose Mortality Among Georgia Prisoners and Releasees: A 2-Decade Cohort Study of Prisoners Incarcerated in 1991

Abstract: Our study design deemphasized immediate deaths but highlighted long-term sequelae of exposure to viral hepatitis and alcohol. Treating hepatitis C and implementing interventions to manage alcohol use disorders may improve survival among prisoners in the Southeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…As described in our prior studies, 6 17 the initial cohort consisted of all persons incarcerated in GA prisons on 30 June 1991. Administrative records containing demographic data and incarceration history were obtained from the GA Department of Corrections (GDC) Planning and Strategic Management Section and linked with the NDI through 31 December 2010.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in our prior studies, 6 17 the initial cohort consisted of all persons incarcerated in GA prisons on 30 June 1991. Administrative records containing demographic data and incarceration history were obtained from the GA Department of Corrections (GDC) Planning and Strategic Management Section and linked with the NDI through 31 December 2010.…”
Section: Methodsmentioning
confidence: 99%
“… 17 The study was recently updated to include deaths through 2010 and found 5% of the population were HIV infected and overall cancer was a close second to heart disease as a leading cause of death among all prisoners regardless of HIV status. 6 …”
Section: Introductionmentioning
confidence: 99%
“…4 The period immediately after release is especially risky for receptive syringe sharing, acquisition of HIV and hepatitis C virus (HCV), and mortality. [29][30][31][32] Thus, the transition between the prison and community settings represents a high-risk…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the corresponding prevalence in US prisons is 17.3% (2). Liver disease is a frequent cause of death in inmates, as well as in society, and it has recently surpassed that from HIV (3-5). Hepatitis C virus (HCV) infection is also the leading cause of hepatocellular carcinoma and the most common indication for liver transplant (6).…”
Section: Introductionmentioning
confidence: 99%